Evaluation of Infection Control Measures in a Public Sector Dental Hospital of Peshawar - Abdullah, Ahmed; Afridi, Saira; Gillani, Syed Imran (Journal of Gandhara Medical and Dental Science, 2015)
Objective: To evaluate infection control measure in a public sector dental hospital of Peshawar. Methodology: It was a cross sectional study conducted in Khyber college of Dentistry. Study subjects were Dental health care providers who were willing to participate in the study. A structured questionnaire was designed that included various categories of infection control. Data was entered into SPSS version 17. Descriptive statistics were applied and frequencies and percentages were obtained. Results: The results from the data shows that the overall score for the infection control standards were less than 50%. Among the various categories of infection control only personal hygiene standards showed good score (77.3%). Personal protective equipment score was adequate (61%) while hand hygiene score was inadequate (52%). The rest of the categories showed poor scores. Conclusion: The result of the study shows that majority of categories of infection control measures at Khyber college of Dentistry are inadequate or poor.